Lipoproteins and cardiovascular reactivity - Howes, Laurence G. (1997)
The observation that relatively short periods of cholesterol lowering therapy can reduce the incidence of coronary artery disease events has prompted interest in the short term effects of lipoproteins on cardiovascular responsiveness. Numerous studies in animals and humans have demonstrated that oxidized LDL-cholesterol can impair endothelial dependent vasodilation in coronary arteries and peripheral resistance vessels. Reduction of plasma LDL-cholesterol levels in hypercholesterolaemic patients improves nitric oxide mediated vasodilator responses in the coronary and peripheral circulation. LDL-cholesterol also potentiates responses to vasoconstrictors such as noradrenaline and endothelin-1 in the absence of endothelium, possibly by enhancing calcium influx into vascular smooth muscle cells. Pharmacological reduction of plasma LDL-cholesterol levels has been shown to reduce blood pressure responses to intravenous infusions of pressor hormones and to stress. However, the relative contribution of changes in endothelial dependent vasodilation and vasoconstrictor or inotropic responses remains to be established. Short term changes in LDL-cholesterol produce changes in cardiovascular responsiveness that may influence the development of ischaemic events.